A‐to‐I editing on tRNAs: Biochemical, biological and evolutionary implications. Issue 23 (27th September 2014) - Torres, Adrian Gabriel; Piñeyro, David; Filonava, Liudmila; Stracker, Travis H.; Batlle, Eduard; Ribas de Pouplana, Lluis
Abstract : Inosine on transfer RNAs (tRNAs) are post‐transcriptionally formed by a deamination mechanism of adenosines at positions 34, 37 and 57 of certain tRNAs. Despite its ubiquitous nature, the biological role of inosine in tRNAs remains poorly understood. Recent developments in the study of nucleotide modifications are beginning to indicate that the dynamics of such modifications are used in the control of specific genetic programs. Likewise, the essentiality of inosine‐modified tRNAs in genome evolution and animal biology is becoming apparent. Here we review our current understanding on the role of inosine in tRNAs, the enzymes that catalyze the modification and the evolutionary link between such enzymes and other deaminases.